Opening the gateway to effective learning: Identifying the need for android-based mobile learning media - Abd Aziz Ardiansyah; Hera Novia; Rudiana Rudiana (Momentum: Physics Education Journal, 2025)
The development of digital technology in the Industrial Revolution 4.0 era has encouraged innovation in education, one of which is through Android-based mobile learning. However, students' mobile learning media use still needs improvement. This research aims to identify special needs in developing physics learning media based on Android applications that can effectively support the teaching and learning process. The method used was a descriptive survey with a mixed-methods approach involving class XI students and high school physics teachers who had implemented technology in learning. Data was collected through questionnaires and semi-structured interviews, which were analyzed thematically and descriptively. The results showed that 90% of students are interested in physics, but 75% find it difficult. As many as 87.5% of students feel more interested when using learning media, and 80% need Android-based applications to increase interest in learning physics. However, only 25% of students have ever used application-based pocketbooks, indicating the low adoption of digital media in physics. This research concludes that developing interactive mobile learning applications that suit student needs and the curriculum is necessary to increase the effectiveness of physics learning. The implications of this research emphasize the need for collaboration between application developers, educators and educational stakeholders to create innovative and relevant learning media. The main recommendation is that schools and educational institutions consider integrating mobile learning applications in the physics curriculum and provide training to teachers to maximize the use of technology in learning.